2023
DOI: 10.3390/v15020355
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Capsid Expansion Mechanism of Bacteriophage P22 Revealed by High-Resolution Cryo-EM Structures

Abstract: The formation of many double-stranded DNA viruses, such as herpesviruses and bacteriophages, begins with the scaffolding-protein-mediated assembly of the procapsid. Subsequently, the procapsid undergoes extensive structural rearrangement and expansion to become the mature capsid. Bacteriophage P22 is an established model system used to study virus maturation. Here, we report the cryo-electron microscopy structures of procapsid, empty procapsid, empty mature capsid, and mature capsid of phage P22 at resolutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…A-domain (a.a. 128–221, 346–357, and 417–430) surrounds the center of the oligomer and has a flexible loop exposed to solvents. It is a region susceptible to protease action in the monomer and the PC, but it becomes more resistant after capsid maturation [ 43 , 48 , 51 , 52 ]. The flexibility of the A-domain allows the manipulation of this region with no repercussions to PC assembly or capsid integrity [ 43 ].…”
Section: The Structure Of the P22 Vlpmentioning
confidence: 99%
See 4 more Smart Citations
“…A-domain (a.a. 128–221, 346–357, and 417–430) surrounds the center of the oligomer and has a flexible loop exposed to solvents. It is a region susceptible to protease action in the monomer and the PC, but it becomes more resistant after capsid maturation [ 43 , 48 , 51 , 52 ]. The flexibility of the A-domain allows the manipulation of this region with no repercussions to PC assembly or capsid integrity [ 43 ].…”
Section: The Structure Of the P22 Vlpmentioning
confidence: 99%
“…One example is residue T183, which is in an axial position on the capsomer, as seen in structural models of P22, making it an interesting target for mutations, especially because it was shown that T183 modifications did not affect capsid assembly [ 51 ]. The P-domain (a.a. 31–33, 79–127, and 358–416) is positioned at the extremity of the protein and forms an important interaction with the N-terminal arm (N-arm) in (a.a. 2–30) that stabilizes the capsid after expansion [ 44 , 52 ]. The E-loop (a.a. 51–78) is a hinge-shaped region, which is a site of crosslinks in HK97 but is shortened on the P22 [ 34 , 52 ].…”
Section: The Structure Of the P22 Vlpmentioning
confidence: 99%
See 3 more Smart Citations